Anisotropic Weak Hardy Spaces and Wavelets. (3rd May 2012) - Barrios, B.; Betancor, J. J.
Abstract : We characterize the anisotropic weak Hardy spaces H A p, ∞ ( ℝ n ) associated with an expansive matrix A by using square functions involving wavelets coefficients.